Analisis Naratif tentang Pengalaman Komunikasi Interpersonal pada Pasangan Muda - Almadina Rakhmaniar (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This study examines the importance of open and honest communication in personal and professional relationships and its impact on group dynamics, team effectiveness, and individual well-being. Through literature review and empirical analysis, it was found that openness in sharing feelings, thoughts, and concerns is key in maintaining healthy and harmonious relationships. Couples who regularly discuss important issues report higher levels of satisfaction in their relationships. Active listening, where full attention is given without distraction, also increases understanding and emotional closeness between couples. However, the study also identified communication challenges such as misunderstandings and conflicts that often trigger disputes, especially among young couples who face difficulties in conveying messages clearly and understanding emotional context. Emotion management during conflict is a major challenge, as many couples find it difficult to remain calm and rational in situations that trigger negative emotions. overcome this challenge, strategies such as using humor and spending quality time together have proven effective. Humor can ease tension and improve mood after conflict, while quality time without technological distractions strengthens bonding and communication. The influence of technology in couples' communication is also reviewed, with an emphasis on the importance of setting boundaries for technology use to avoid misunderstandings and loss of emotional nuance. Social support from family and friends was found to play an important role in helping couples overcome conflict and strengthen their relationship. Couples who had a strong support network felt more confident and optimistic about the future of their relationship. In addition, the evolution of communication in relationships suggests that couples learn to communicate more effectively and efficiently over time, with improved communication skills such as empathy, emotion management, and constructive problem solving.